2011
DOI: 10.1071/zo12016
|View full text |Cite
|
Sign up to set email alerts
|

Do experimental methods affect estimates of pollen digestion by birds?

Abstract: Pollen protoplasts may supply important nutritional resources for birds; however, they are locked up within the mechanically strong and biochemically complex pollen wall. Previous studies of pollen digestion in birds have yielded highly variable and often contradictory results. We tested whether these differences could reflect the vastly different methodologies that have been used. We used a standard method to investigate digestion of Banksia grandis (Proteaceae) pollen in New Holland honeyeaters (Phylidonyris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The most common explanations invoke birds' ( i ) high mobility, which may provide long‐distance pollen dispersal and thus higher gene flow (Stiles, 1978a; Cronk & Ojeda, 2008; Krauss et al ., 2017; Pauw, 2019), and ( ii ) reliable flower visitation in areas with flight conditions too cold or wet for insects (Stiles, 1978a; Cronk & Ojeda, 2008), such as high‐elevation cloud forests or deep, shady canyons (Cruden, 1972; Stebbins, 1989; Dalsgaard et al ., 2009). Another hypothesized advantage is reduced pollen loss; unlike bees, which gather pollen to feed their offspring, birds adapted for nectar‐feeding do not visit flowers to consume pollen (Martínez del Rio, 1994; Fleming et al ., 2012) and do not groom pollen grains into pollen‐carrying structures while foraging (Nicolson, 2007b). Thus, birds may transfer more pollen to subsequently visited plants (Thomson & Wilson, 2008; Krauss et al ., 2017), as supported by experiments comparing pollen carryover in hummingbirds versus bumblebees (Waser, 1988; Castellanos, Wilson & Thomson, 2003).…”
Section: The Evolution Of Bird Pollinationmentioning
confidence: 99%
“…The most common explanations invoke birds' ( i ) high mobility, which may provide long‐distance pollen dispersal and thus higher gene flow (Stiles, 1978a; Cronk & Ojeda, 2008; Krauss et al ., 2017; Pauw, 2019), and ( ii ) reliable flower visitation in areas with flight conditions too cold or wet for insects (Stiles, 1978a; Cronk & Ojeda, 2008), such as high‐elevation cloud forests or deep, shady canyons (Cruden, 1972; Stebbins, 1989; Dalsgaard et al ., 2009). Another hypothesized advantage is reduced pollen loss; unlike bees, which gather pollen to feed their offspring, birds adapted for nectar‐feeding do not visit flowers to consume pollen (Martínez del Rio, 1994; Fleming et al ., 2012) and do not groom pollen grains into pollen‐carrying structures while foraging (Nicolson, 2007b). Thus, birds may transfer more pollen to subsequently visited plants (Thomson & Wilson, 2008; Krauss et al ., 2017), as supported by experiments comparing pollen carryover in hummingbirds versus bumblebees (Waser, 1988; Castellanos, Wilson & Thomson, 2003).…”
Section: The Evolution Of Bird Pollinationmentioning
confidence: 99%
“…In the wild, he main protein source in lorikeet diets is pollen (Smith & Lill, 2008). Supplementing their nectar diet with pollen (Fleming & Moore, 2012) insects or spiders is therefore important, especially during seasons when the birds are moulting or breeding (Nicolson & Fleming, 2014). In order to meet the protein requirement for the birds, therefore the palm sugar solution as the primary diet should be added with other food as a protein source.…”
Section: Amino Acid Compositionmentioning
confidence: 99%
“…Nitrogen levels found in most floral nectars are generally insufficient to meet the nitrogen requirements of nectarivorous vertebrates (López-Calleja et al, 2003). Supplementing their nectar diet with pollen (Fleming and Moore, 2012), insects or spiders is therefore important, especially during seasons when the birds are moulting or breeding. A reasonably recent review (Tsahar et al, 2006) concluded that nectarivores and frugivores have nitrogen requirements only ~25% of that of omnivorous birds.…”
Section: How Do Nectarivorous Birds Deal With Low Protein Intake?mentioning
confidence: 99%